Applied Failure Modes and Effects Analysis for Improve Maintenance System for Yarn Twisting Machine: A Case Study of Yarn Manufacturing - Phieboolsilapa, Sawitree; Chongchaem, Giattikul; Rassameesoraj, Nattapat; Klomjit, Prachuab (Journal of Advanced Development in Engineering and Science, 2026)
This research aims to apply Failure Mode and Effects Analysis (FMEA) to reduce the risk of machine failures during operation, improve the maintenance system, and minimize waste in the yarn twisting production process. The examination of defect data from the case study company revealed that the major defects were dirty yarn, fuzzy yarn, and crossed threads. A fishbone diagram was used to analyze the causes and effects of these issues. After identifying the failure modes and their impacts, the Risk Priority Number (RPN) was calculated. High-risk defects were prioritized for improvement. The main area identified for improvement was the maintenance system, which was enhanced using Total Productive Maintenance (TPM) techniques, specifically Autonomous Maintenance (AM) and Focused Improvement (FI). As a result, the defect rate decreased from 1.18% to 0.39%, representing a 66.95% reduction in defects.